2018
DOI: 10.1016/j.chempr.2017.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyzer Design for Flexible Decoupled Water Splitting and Organic Upgrading with Electron Reservoirs

Abstract: Robust proton-independent electron reservoirs of (ferrocenylmethyl) trimethylammonium chloride and Na 4 [Fe(CN) 6 ] are utilized to separate H 2 evolution from O 2 evolution with much lower voltage inputs than that of conventional water-splitting electrolysis. Such decoupled water splitting can be readily driven by photovoltaics with small photovoltages in near-neutral solution under natural sunlight irradiation. The electron reservoirs can facilitate sustainable H 2 production from decoupled water splitting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
131
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(136 citation statements)
references
References 49 publications
0
131
0
5
Order By: Relevance
“…Based on the above consideration, Sun et al recently reported an alternative strategy of utilizing Na 4 [Fe(CN) 6 ] as a low‐cost proton‐independent redox mediator for decoupled water splitting in alkaline electrolytes . Na 4 [Fe(CN) 6 ] has a great solubility in alkaline electrolyte (1.0 M KOH) and rapid electron transfer kinetics on electrode.…”
Section: Decoupled Water Splitting In Basic Electrolytementioning
confidence: 99%
See 3 more Smart Citations
“…Based on the above consideration, Sun et al recently reported an alternative strategy of utilizing Na 4 [Fe(CN) 6 ] as a low‐cost proton‐independent redox mediator for decoupled water splitting in alkaline electrolytes . Na 4 [Fe(CN) 6 ] has a great solubility in alkaline electrolyte (1.0 M KOH) and rapid electron transfer kinetics on electrode.…”
Section: Decoupled Water Splitting In Basic Electrolytementioning
confidence: 99%
“…b) Linear sweep voltammograms of a Co−P working electrode with (red) and without (blue) 0.3 M Na 4 [Fe(CN) 6 ] in the counter chamber. c) Linear sweep voltammograms of a Ni foam working electrode with (red) and without (black) 0.3 M Na 3 [Fe(CN) 6 ] in the counter chamber in the absence (red and black) and presence (green) of 10 mM HMF in the working chamber . Reproduced with permission from Ref.…”
Section: Decoupled Water Splitting In Basic Electrolytementioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, such an innovative electrolysis system could lower the voltage input and exclude the formation of H 2 /O 2 gas mixture and reactive oxygen species due to the replacement of OER with thermodynamically more favorable anodic oxidation reactions . On the other hand, value‐added anodic products instead of O 2 can be potentially produced at the anode side of the system by choosing suitable feedstock chemicals, maximizing the return of energy investment …”
Section: Introductionmentioning
confidence: 99%